A Novel Multi-Port Containment System for Laparoscopic Power Morcellation to Prevent Tumoral Spread: A Retrospective Cohort Study - Wang, Wenhui; Liang, Haiyan; Zhao, Fang; Yu, Huan; Rong, Chunhong; Feng, Weiwei; Chen, Qingyun; Yang, Yanjun; Li, Qian; Feng, Dingqing; Dong, Yuxiao; Xue, Ming; et al. (Frontiers in Surgery, 2022)
Objective To report a novel multi-port containment (NMC) system for laparoscopic power morcellation to prevent tumoral spread and to evaluate its safety, validity, and feasibility. Methods This retrospective study included women who underwent laparoscopic myomectomy (LM) between January 2014 and August 2020 at a single academic institution. The NMC system was used in the study group (n = 193); the control group underwent unprotected LM (n = 1753). Results After 1:1 propensity score matching, no significant differences in the baseline characteristics were observed between 193 matched pairs. Bag damages were detected in two cases in the study group before morcellation, and the NMC systems were replaced. There were no significant differences between the two groups in terms of the complications, total operative time, estimated blood loss, or postoperative hospitalization duration. In the study group, all operations were completed and no system rupture or leakage was observed. The median follow-up times were 21 and 54 months in the study and control groups, respectively. There was no peritoneal tissue spread in the study group. However, three (3/5, 0.6%) and six (6/1,753, 0.3%) patients in the control group experienced malignant and benign peritoneal tissue spread, respectively. Conclusion The NMC system for laparoscopic power morcellation is valid, safe, and feasible for preventing a tumor spread.